Friend or foe? Flankers reverse the direction of orthographic neighbourhood effects. Issue 5 (1st June 2021) - Meade, Gabriela; Grainger, Jonathan; Declerck, Mathieu
ABSTRACT: Increasing the neighbourhood density of a word typically facilitates lexical decision responses and interferes in sentence reading. The Multiple Read-Out Model accounts for such variation by postulating that word responses in the lexical decision task can be made via two mechanisms – identifying the word or using the global lexical activity that it generates. Here, we asked whether adding unrelated flanking words to either side of the target would modulate the relative contribution of these two mechanisms. That is, do flankers promote the use of word identification processes that are more characteristic of sentence reading? In line with our hypothesis, in Experiment 1 flanker words increased the inhibitory influence of orthographic neighbours relative to single word presentation. In Experiment 2, flanker neighbourhood density did not affect lexical decisions to central targets. This pattern indicates that the mechanisms used to make a lexical decision can be modulated by a minimal "sentence-like" context.